178k views
0 votes
Which of the following is equal to the expression when x does not equal -2 or 3?

Which of the following is equal to the expression when x does not equal -2 or 3?-example-1
User Ackeem
by
5.7k points

2 Answers

4 votes

Answer:

x+3/x-3

Step-by-step explanation:

User Gabriel Rohden
by
5.5k points
6 votes

Answer:

at first we should simplify each equation by find its roots

(x^2+5x+6) =

(x+2) (x+3)

(x^2-x-6)=

(x-3) (x+2)

sox^2+5x+6÷x^2-x-6=

(x+2)(x+3)÷(x-3)(x+2)=

A(x+3) ÷(x-3)

User InBetween
by
5.3k points